Targeting hypoxia-inducible factors for breast cancer therapy: A narrative review - Luo, Shuang; Jiang, Yu; Anfu Zheng,; Zhao, Yueshui; Wu, Xu; Li, Mingxing; Du, Fukuan; Chen, Yu; Deng, Shuai; Chen, Meijuan; Li, Wanping; Li, Xiaobing; et al. (Frontiers in Pharmacology, 2022)
Hypoxia-inducible factors (HIFs), central regulators for cells to adapt to low cellular oxygen levels, are often overexpressed and activated in breast cancer. HIFs modulate the primary transcriptional response of downstream pathways and target genes in response to hypoxia, including glycolysis, angiogenesis and metastasis. They can promote the development of breast cancer and are associated with poor prognosis of breast cancer patients by regulating cancer processes closely related to tumor invasion, metastasis and drug resistance. Thus, specific targeting of HIFs may improve the efficiency of cancer therapy. In this review, we summarize the advances in HIF-related molecular mechanisms and clinical and preclinical studies of drugs targeting HIFs in breast cancer. Given the rapid progression in this field and nanotechnology, drug delivery systems (DDSs) for HIF targeting are increasingly being developed. Therefore, we highlight the HIF related DDS, including liposomes, polymers, metal-based or carbon-based nanoparticles.